Human-Monkey Conflict in India:Some Available Solutions for Conflict Mitigation with Special Reference to Himachal Pradesh - Reddy, A. R. M.; Chander, Jagdish (Indian Forester, 2016)
'Monkey Management' is the most challenging issue, the forest and wildlife managers of India are facing today. On one hand monkeys have cultural, scientific and economic significance, on the other hand they have become a big nuisance as on today. The monkeys are leaving forests and are constantly migrating to urban, semi urban and rural areas. because of their shrinking habitat, and availability of delicious and easy food in urban areas. Human-monkey conflict has today attained a serious proportion. The human-monkey conflict management includes use of bioacoustics that produce distress noise and to scare away the monkeys, Immunocontraceptive vaccines, sterilization to control their population growth and protecting agriculture crops and orchards with live/appropriate fencing etc. The future management strategies could include oral contraceptives which can be fed with food, though their effectiveness is limited to only zoos. Himachal Pradesh (HP), which is the most affected due to Rhesus macaque, has resorted to sterilizing Rhesus. Himachal Pradesh Forest Department (HPFD) is well convinced with the success of monkey sterilization programme and is set to sterilize most of Rhesus population of the state. However, a change in the behaviour of sterilized monkeys has been observed and therefore, HPFD has been constantly proposing establishing 'Vanar Vatikas' (monkey shelter homes) with proper facilities for drinking water, shade, resting, feeding and ranging. An account of non human primate species found in India, human-monkey conflict mainly due to Rhesus macaque (Macaca mulatta) and status of its management in India with special reference to its sterilization programme in Himachal Pradesh has been discussed in the paper.